Cesarean section predominantly affects right ventricular diastolic function during the early transitional period - Katsuo Tao; Yoshikazu Hara; Yasunori Ishihara; Yusei Ohshima (Elsevier, 2019)
Background: Although the mode of delivery is well known to affect pulmonary function, the effects of a cesarean delivery on postnatal changes in cardiac mechanics have not been clearly defined. Methods: To evaluate whether delivery mode influences cardiac function in the early transitional period, 42 infants delivered by cesarean section (CS) and 110 by vaginal delivery (VD) were enrolled, and they underwent serial echocardiography at 0, 1, 2, and 5 days of age. Longitudinal changes in ejection fraction (EF), fractional area change (FAC), mitral annular plane systolic excursion (MAPSE), tricuspid annular plane systolic excursion (TAPSE), Tei index, ratio of peak early diastolic flow velocity (E) to peak early diastolic annular velocity (e') (E/e'), and deceleration time (DcT) were compared between the two groups. Results: FAC and DcT of both ventricles increased during the first week, whereas Tei index of each chamber decreased irrespective of delivery mode. E/e's of both ventricles were significantly higher and MAPSE was significantly lower in the CS than VD group throughout the observation period. After adjustment for the effects of birth weight, gestational age, and oxygen administration by multivariate analysis, right ventricular E/e', which reflects diastolic function of the right ventricle, was most affected by delivery mode. Conclusion: CS affected diastolic function of the right ventricle in the 2nd day after giving birth and did not persist. Delayed adaptation of the neonatal myocardium and/or persistence of pulmonary hypertension might explain the hemodynamic changes in neonates born by CS. Key Words: cesarean section, echocardiography, ventricular function